Social Participation Among Older Adults Receiving Community Care Services. (September 2021) - Siette, Joyce; Berry, Helen; Jorgensen, Mikaela; Brett, Lindsey; Georgiou, Andrew; McClean, Tom; Westbrook, Johanna
Aged care services have the potential to support social participation for the growing number of adults aging at home, but little is known about the types of social activities older adults in community care are engaged in. We used cluster analysis to examine the current profiles of social participation across seven domains in 1, 114 older Australians, and chi-square analyses to explore between-group differences in social participation and sociodemographic and community care service use. Two distinct participation profiles were identified: (a) connected, capable, older rural women and (b) isolated, high-needs, urban-dwelling men. The first group had higher levels of engagement across six social participation domains compared with the second group. Social participation among older adults receiving community care services varies by gender, age, individual care needs, and geographical location. More targeted service provision at both the individual and community levels may assist older adults to access social participation opportunities.